'An Absolutely Private Thing': Letters in Kate O'Brien's The Land of Spices. Issue 1 (May 2018) - Sullivan, Kelly
Abstract : Kate O'Brien's 1941 The Land of Spices navigates spatial and emotional gaps through a series of letters that punctuate the narrative and offer evidence of the inner life of protagonist Helen Archer. Yet these letters also interrupt our reading experience in crucial ways, forcing us to consider the risks inherent in public writing, and the value of privacy a letter affords. Letters signal to us two motivating factors in the novel: a claim to absolute individual privacy, and, related to that claim, the ethical imperative to acknowledge social and political pressures and to engage with historical events. Through epistolary transactions and a twinned bildungsromane structure, O'Brien emphasizes that privacy and free will cannot be intellectually removed from social and political engagement. The Land of Spices uses letters to comment on the role of literature at a time of crisis, and the responsibility of Ireland in Europe as the continent descends into World War.